A case of familial syndactyly associated with eye and dental abnormalities. Issue 12 (December 2015) - Mills, Janith K.; Wheeler, Lesley; Oishi, Scott N.
Abstract : ABSTRACT: Syndactyly occurs in 1 in 2, 000 live births and is more common in white children. This article describes a patient with syndactyly and additional abnormalities indicating oculodentodigital dysplasia.